2004
DOI: 10.3121/cmr.2.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovarian Syndrome: Diagnosis and Management

Abstract: Polycystic ovarian syndrome (PCOS) affects 4% to 12% of women of reproductive age. The lack of well-defined diagnostic criteria makes identification of this common disease confusing to many clinicians. Also, with the varied manifestations of the disorder a patient may present to any one of several providers: an internist, family practitioner, nurse practitioner, pediatrician, gynecologist, dermatologist, or endocrinologist. Furthermore, the most distressing aspect of PCOS for any given patient may change over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
155
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(170 citation statements)
references
References 152 publications
6
155
0
9
Order By: Relevance
“…Clinical manifestations of PCOS include oligomenorrhea/amenorrhea, infertility/first trimester miscarriage, obesity, hirsutism, acne, acanthosis nigricans and male pattern alopecia. 5 Clomiphene resistance is common and occurs in approximately 15%-40% of women with PCOS. 6 Clomiphene resistance is defined as failure to ovulate after receiving up to 150 mg of clomiphene citrate (CC) daily for 5 days from 2nd day of cycle for at least 3 menstrual cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical manifestations of PCOS include oligomenorrhea/amenorrhea, infertility/first trimester miscarriage, obesity, hirsutism, acne, acanthosis nigricans and male pattern alopecia. 5 Clomiphene resistance is common and occurs in approximately 15%-40% of women with PCOS. 6 Clomiphene resistance is defined as failure to ovulate after receiving up to 150 mg of clomiphene citrate (CC) daily for 5 days from 2nd day of cycle for at least 3 menstrual cycles.…”
Section: Introductionmentioning
confidence: 99%
“…It is a common disorder affecting 4-12% of women of reproductive age (1,2) . PCOS was first described in the United States in 1935 (3) , and it is characterized by chronic anovulation and hyperandrogenism in the absence of underlying adrenal or pituitary disease (4) .…”
Section: Introductionmentioning
confidence: 99%
“…In a systemic review and meta-analysis it was shown that women with PCOS had a greater risk of overweight, obesity, and central obesity 8 . Lack of exercise and low physical activity may play a significant role in the rise in prevalence of PCOS 9 .The rate of obesity in the PCOS population ranges from 38% to 87% 10 . We found an increase in the waist circumference observed in the normal control women compared to PCOS subjects in our taken population.…”
Section: Discussionmentioning
confidence: 99%